THE IMPLEMENTATION OF GAME TO INCREASE COURAGE CHILDREN TO SPEAKING ENGLISH IN DAHANREJO VILLAGE GRESIK - Hidayanti Qurani, Risca; Kurnia, Safira Dewi; Bhakti, Henny Dwi; Rahim, Andi Rahmad; Sukaris, Sukaris; Fauziyah, Nur (DedikasiMU(Journal of Community Service), 2021)
This study aims to increase courage children to speaking English using implementation of game in Dahanrejo village, Kebomas, Gresik. The author as tutors and teachers for children in Dahanrejo village in this research. The problems refer to in Dahanrejo village, many children are afraid to speak English because there are no motivation to increase knowledge related studying English, therefore they have lack vocabulary and also teachers can’t explore the other media to teaching English in the classroom. The results of the action research given by the authors are the application of the media can improve the English language skills especially speaking of students and be able to provide variations in indoor learning that are not only fixed on the Package Books and Students Worksheets (LKS). Not only that, but the authors also found that the media was able to change the mood of students who did teaching through the media and were more interested in English.